Effectiveness of social prescribing programs in the primary health-care context: a systematic literature review - Costa, Andreia (2021)
Social prescribing (SP) is an approach that promotes the use of local non-clinical activities by people. The referral is usually made by primary health-care professionals, in a process wherein local providers play a pivotal role. The main objective of this study was to identify domains of intervention and evidence about the effectiveness of SP programs regarding health-related outcomes. A systematic literature review was carried out following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A literature search was conducted in PubMed, CINHAL, and SCOPUS. Inclusion criteria of the reviewed papers were as follows: (i) effectiveness studies of interventions designated as SP or interventions entailing SP conceptual components; (ii) interventions with adults. Quality assessment was performed with the Cochrane tool for assessing risk of bias in randomized trials; an assessment tool developed by the US National Heart, Lung and Blood Institute was applied to observational studies. Overall, 13 articles were included for analysis, with a total of 4603 patients. Although three studies comprised a control group, only two followed a randomized controlled trials (RCT) design. Nine principal domains of intervention within SP were identified, with three categories of outcome measures: Physical and psychological wellbeing; Health behaviors and self-efficacy; and Health care resources end economic evaluation. SP is an emergent and promising health-care intervention, and it has been used to promote different health behaviors. Evidence of SP effectiveness on patient’s health and wellbeing is not strong. Further research is needed for understanding how SP can be applied efficiently.